Lazarus Effect of High Dose Corticosteroids in a Patient With West Nile Virus Encephalitis: A Coincidence or a Clue? - Leis, A. Arturo; Sinclair, David J. (Frontiers in Medicine, 2019)
West Nile virus (WNV) causes severe neuroinvasive disease in humans characterized by meningitis, encephalitis, and acute flaccid paralysis (poliomyelitis variant). In neuroinvasive disease, WNV infection of neurons resulting in neuronal loss is generally presumed to be the anatomical substrate for the high morbidity and mortality. However, on a molecular level, WNV infection also results in a significant upregulation of important proinflammatory molecules that have been reported to promote neuroinflammation and cytotoxicity. Currently, there is no specific treatment for the neurological complications of WNV infection. We present a 71-year-old woman who developed WNV infection that rapidly progressed to severe generalized weakness and encephalitis manifesting with bulbar signs (dysphagia, dysarthria) and persistent delirium and stupor. Consciousness remained impaired for 9 days and then she received a 5-day course of high-dose intravenous methylprednisolone (1,000 mg daily). After the first day, voluntary movement and spontaneous eye-opening increased and by the end of the second day, she was awake and responding to commands. Thereafter, she remained awake and responsive. Although the rapid improvement from stupor to wakefulness following treatment with an anti-inflammatory immunosuppressant could merely be coincidence, since these observations are of one patient, it may also provide a clue that in some cases of WNV neuroinvasive disease, a post-infectious pro-inflammatory state, rather than neuronal loss, may also contribute to morbidity. Further clinical trials are warranted to determine if high dose corticosteroids and other drugs that can alter this neuro-inflammatory cascade may be potentially beneficial in the treatment of WNV neuroinvasive disease.